Ultrasound-Assisted, Transition-Metal-Free Synthesis of Diaryl Tellurides from Aryl Boronic Acids: A Possible Free-Radical Mechanism - Mohan, Balaji; Hwang, Sori; Jang, Seongwan; Park, Kang Hyun (Synlett, 2014)
The first rapid, catalyst-free synthesis of diphenyl tellurides from readily available diphenyl ditelluride and aryl boronic acids is reported. The high efficiency, general applicability and wide substrate scope, including heterocycles and other functional groups, make this method superior. The technique, which utilizes dimethyl sulfoxide solvent and ultrasound promotion, opens the door for the synthesis of diphenyl tellurides at 100 °C in air within a short time in high yields.
Keywords: arylation; cross-coupling; free radicals; diphenyl telluride; transition metals